Building information modeling technology foundations and industry practice - Borrmann, André 1978-; König, Markus 1971-; Koch, Christian 1979-; Beetz, Jakob 1974- (Springer, 2018)
Building Information Modeling (BIM) refers to the consistent and continuous use of digital information throughout the entire lifecycle of a built facility, including its design, construction and operation. In order to exploit BIM methods to their full potential, a fundamental grasp of their key principles and applications is essential. Accordingly, this book combines discussions of theoretical foundations with reports from the industry on currently applied best practices.The books content is divided into six parts: Part I discusses the technological basics of BIM and addresses computational methods for the geometric and semantic modeling of buildings, as well as methods for process modeling. Next, Part II covers the important aspect of the interoperability of BIM software products and describes in detail the standardized data format Industry Foundation Classes.-
Keywords: Building Information Modeling; Computer aided design; Civil engineering; Architecture; Software engineering; Computer science; Applied Computing in Architecture; BIM - Building Information Modeling; BIM Use Cases; Computer-Aided Engineering; Construction Management; Technology Management; Aufsatzsammlung